KECURANGAN LAPORAN KEUANGAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Fatmawati, Rima; Prasetiyo, Hermawan Budi; Bisri, Hasan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
Companies always desire to increase their value to attract investors, but sometimes they manipulate financial reports so they always look good every year. This study aims to determine the effect of financial stability, external pressure, personal financial needs, and financial targets for indications of financial statement fraud. The research population totaled 27 companies selected using a purposive sampling technique, obtaining ten companies with three years of observation, namely 2019-2021, and using multiple linear regression data analysis techniques. The results show that financial stability has a positive effect, while external pressure, personal financial needs, and financial targets do not affect indications of financial statement fraud. Simultaneously, financial stability, external pressure, personal financial needs, and financial targets have a positive effect with a significance value of 0.038 on indications of fraud in financial reports on food and beverage sub-sector companies listed on the IDX in 2019-2021.